Boron‐Rich Boron Nitride Nanotubes as Highly Selective Adsorbents for Selected Diatomic Air Pollutants: A DFT Study. Issue 4 (25th January 2022) - Bae, Hyeonhu; Hussain, Tanveer; Choi, Heechol; Lee, Hoonkyung
Abstract: Boron‐rich boron nitride nanotubes (BN ‐BNNTs), which have boron antisite defects (BN ), adsorb gas molecules more favorably as compared to their pristine counterparts because of the localized states of antisites. Using computational chemistry methods, the structural, adsorptive, and electronic properties of selected diatomic air pollutants (CO, NO, and SO) on BN ‐BNNT (8, 0), with a particular focus on the antisites, are investigated. It is found that CO adsorbs on BN with 180° angle (∠BN CO) while NO and SO adsorb with 142° angle (∠BN NO) and 116° angle (∠BN SO), respectively. This difference is ascribed to the repulsive interaction originated from lone pair electrons on N and S. Adsorption energy of CO, NO, and SO molecules dominates over that of O2 and N2 and is independent of their radii of BN ‐BNNTs. The practical capacity of these pollutant molecules is calculated to be ≈5 mmol g –1 (14 wt%) under ambient conditions. Therefore, our results show that BN ‐BNNT can be used as a highly selective adsorbent for diatomic air pollutants. BN ‐BNNT as sensing materials in terms of change in bandgap and work function through the adsorption is also discussed. Abstract : Boron‐rich boron nitride nanotubes (BN ‐BNNTs), which have boron antisite defects (BN ) have great selectivity for diatomic air pollutants, such as CO, NO, and SO. Practical capacity of these pollutant is calculated to be ≈5 mmol g −1 under ambient conditions, and it is maintained for nanotubes of any radii, which offers advantage as there is no need to control the size of BNNT.